Antikapitalisme dalam Antologi Puisi “Nyanyian Akar Rumput” Karya Wiji Tukul dan Kontribusinya terhadap Pembelajaran Puisi di SMA Kelas X (Analisis Wacana Kritis) - Alfiansyah Sachran; Azis Azis; Hajrah Hajrah; Andi Agussalim AJ (Indonesian Journal of Social and Educational Studies, 2021)
Abstract. This research is a qualitative descriptive study that carefully analyzes the poetry anthology of Nyanyian Akar Rumput by Wiji Tukul. The purpose of this study was to describe the form of vocabulary, grammar, and text structure of anti-capitalism in Wiji Tukul's poetry anthology Nyanyian Roots and its contribution to poetry learning in SMA Class X. The instrument of this research was research worksheets and researchers. The data of this research are in the form of words, expressions, phrases and clauses that contain anti-capitalism, while the data source used is the anthology of poetry Nyanyian Akar Rumput by Wiji Tukul. Data collection techniques are reading, documentation, and note-taking methods. Data were analyzed through data collection, data processing, data presentation, and drawing conclusions. The results of the analysis show that (1) aspects of vocabulary that contain elements of anti-capitalism include the use of synonyms, antonyms, hyponyms, euphemistic expressions, formal vocabulary, expressive values, and metaphors. These aspects can be used as a medium for learning poetry in high school class X; (2) grammatical aspects that contain elements of anti-capitalism in the form of agents, numbers, declarative models, grammatical questions, and our relational modalities. These aspects can be used as a medium for learning poetry in high school class X; and (3) aspects of the structure of the text that contain elements of anti-capitalism including one-way communication, interruptions, and formulations. These aspects can be used as a medium for learning poetry in high school class X. Keywords: Anti-capitalism, Poetry, Vocabulary, Grammar, Text Structure